Business Model Canvas Implementation on the Performance of MSMEs in Rural Areas - Cuk Jaka Purwanggono (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study investigates the influence of implementing the business model canvas on the performance of micro, small, and medium enterprises in rural areas. The Business Model Canvas integrates nine components of business design, including customer relationship, customer segment, cost structure, channel, key activities, key partners, key resources, revenue stream, and value proposition. The objective of this study is to analyze how the structured use of these elements can strengthen business effectiveness and competitiveness within rural development contexts. A quantitative research method was applied through the distribution of questionnaires to business owners in rural communities. The collected data were analyzed using the partial least squares structural equation modeling method to examine the relationship between the implementation of the business model canvas and enterprise performance. The results indicate that the structured application of the business model canvas significantly improves the performance of micro, small, and medium enterprises. Enhanced partnerships, effective communication channels, and strong customer value propositions are identified as major contributors to better organizational outcomes. Practically, this study provides useful insights for policymakers and development agencies in formulating strategic management initiatives that support innovation, efficiency, and adaptability in rural entrepreneurship.